(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: At the time of diagnosis most of the pancreatic caner is well advanced and curative resection becomes impossible. These are labeled as unresectable carcinoma pancreas where only palliative medical or surgical measures could be done. Objectives: To observe the various types of palliations with their early result. Methods: This retrospective study was carried out in the department of Hepato-Biliary-Pancreatic Surgery in BIRDEM hospital, Dhaka, Bangladesh from July 2004 to June 2006. After careful check 50 patients were labeled as unresectable carcinoma pancreas. Surgical intervention was thought impossible in 10 patients and these patients took only chemotherapy. Laparotomy was carried out in the rest 40 patients with the plan to take open biopsy along with surgical palliation. Curative resection was seemed not to be possible in any patient. After abdominal exploration resectability of the pancreatic lesion was assessed and compared with prior plan. Post operative histopathology revealed pancreatic carcinoma in 35 patients. Postoperative treatment modalities used like chemotherapy, chemoradiation were assessed. Overall outcome of all the palliations were noted and compared with initial presentations. Result: Among 50 patients male were 28 (n1) & female were 22 (n2) with male female ratio was 1.27:1. Eighty percent (80%) patients presented between 51 to 70 years of age. Preoperative plan of surgical palliation noted to be changed significantly after laparotomy. Curative resections were possible in 2 patients. No palliative surgery was possible in 2 patients with gross disease and only biopsy was taken. Palliative surgeries along with biopsy were done in 36 patients. Only biliary bypass carried out in 04 patients, choledochojejunostomy with gastrojejunostomy were performed in 18 patients and hepatico- jejunostomy with gastrojejunostomy were performed in 12 patients. Only gastrojejunostomy were carried out in 02 patients to relieve duodenal obstruction. For pain control chemical splanchnicectomy done in 07 patients.There was no perioperative mortality. Early post operative complications were wound infection in 6 (15%) patients, haemorrhage in 2 (5%) patients and bilioenteric anastomotic leakage in 1(2.5%) patient. Post operative histopathology reports revealed pancreatic carcinoma in 35 patients. After one year follow up it was noted that jaundice again developed in 02 patients (4.6%) underwent choledochojejunostomy and gastrojejunostomy. Control of pain was satisfactory in 31 patients (72.1%) by multimodal analgesia. Chemical splanchnicectomy was satisfactory in 4 (56%) patients to control pain. Twenty seven patients (54%) had died within a year. Only 16 (36%) patients were alive after one year. Seven patients (14%) had lost from follow up. Conclusion: Surgical palliation along with other medical palliations is recommended for unresectable carcinoma pancreas. J. Paediatr. Surg. Bangladesh 3(1): 18-25, 2012 (January)